Pediatric tuberculosis in Iran: a review of 10-years study in an Iranian referral hospital - Movahedi, Zahra; Mahmoudi, Shima; Banar, Maryam; Pourakbari, Babak; Aziz-Ahari, Alireza; Ramezani, Amitis; Mamishi, Setareh (Acta Biomedica Atenei Parmensis, 2022)
Introduction: Reductions in global tuberculosis incidence are considered as one of the End TB Strategy goal. The diagnosis of tuberculosis (TB) in children is challenging due to insufficient specimen material and the scarcity of bacilli in specimens. The purpose of this study was to evaluate the prevalence, characteristics, clinical profiles, laboratory findings and treatment outcomes of children infected with TB in an Iranian referral hospital during a 10-years period. Methods: This study was a retrospective analysis of the medical records of 90 children (£15 years) with a diagnosis of tuberculosis who were admitted to Children’s Medical Center Hospital, Tehran, Iran, between March 2006 and March 2016. The patients’ information such as demographic, clinical manifestations, laboratory, radiological and histological tests results, and treatment outcomes were extracted from medical records and were analyzed. Results: The total prevalence of TB was about 56.6 per 100,000 admitted patients. Most of the patients were between 5 to 12 years. Sixty-one percent were male. Twenty-two percent had the history of TB in their family. Underlying diseases were identified in 30 cases (33%). Thirty-four cases (38%) had pulmonary TB (PTB), 35 cases (39%) had extrapulmonary TB (EPTB), while disseminated TB (DTB) was found in 21 cases (23%). Distribution of DTB in males was higher than in females (36% vs. 6%). In patients < 1 year, DTB was the most frequent type (48 %); however, in patients > 1 year both PTB and EPTB had similar distributions (42%) and were more frequent than DTB (16%). Conclusions: The total prevalence rate of TB in our study was 56.6 per 100,000 admitted patients. Since the mortality rate was higher in infants, children with DTB and children with underlying diseases, early detection and treatment of these patients will help to reduce the mortality rate of TB disease.